2017
DOI: 10.1371/journal.pcbi.1005358
|View full text |Cite
|
Sign up to set email alerts
|

How evolution learns to generalise: Using the principles of learning theory to understand the evolution of developmental organisation

Abstract: One of the most intriguing questions in evolution is how organisms exhibit suitable phenotypic variation to rapidly adapt in novel selective environments. Such variability is crucial for evolvability, but poorly understood. In particular, how can natural selection favour developmental organisations that facilitate adaptive evolution in previously unseen environments? Such a capacity suggests foresight that is incompatible with the short-sighted concept of natural selection. A potential resolution is provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
144
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(156 citation statements)
references
References 71 publications
4
144
1
2
Order By: Relevance
“…Example prediction: Short-term selection can increase long-term evolvability if it benefits from an appropriate inductive bias, for example, that the genotype-phenotype map is complex enough to represent structure (epistatic interactions) in the selective environment but simple enough to avoid overfitting that structure [51,53] 2. Can ecosystem functions be adapted without ecosystem selection?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Example prediction: Short-term selection can increase long-term evolvability if it benefits from an appropriate inductive bias, for example, that the genotype-phenotype map is complex enough to represent structure (epistatic interactions) in the selective environment but simple enough to avoid overfitting that structure [51,53] 2. Can ecosystem functions be adapted without ecosystem selection?…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the possibility that evolution can learn from experience to favourably bias future exploration need not be any more mysterious than the basic result that learning from a training set can produce good generalisation on an unseen test set [51]. This also sheds light on the tension between robustness and evolvability.…”
Section: [ 4 _ T D $ D I F F ] Evo-devo: the Evolution Of Evolvabilitmentioning
confidence: 99%
See 1 more Smart Citation
“…Catastrophic forgetting (French, 1999) is a common problem in machine learning, whereby a learner must forget something in order to learn something new. Third, complex predictive models and dense, non-modular networks can suffer from the pathology of overfitting: they fail to generalize to novel environments (Kouvaris et al, 2015). Modular networks can avoid overfitting by internally reflecting the modularity in its environment: it responds appropriately in a "new" environment, which is actually just an unfamiliar combination of familiar percepts.…”
Section: Non-embodied Modularitymentioning
confidence: 99%
“…random variation and selection) on gene regulatory networks (GRNs) underlying cell plasticity and cell differentiation can exhibit comparable learning capabilities is a non-trivial question. Although during the last years it has been shown that learning principles operate across a plethora of biological phenomena [21]- [26], it remains unknown if these principles apply to plastic cells performing categorisation learning tasks. Furthermore, most studies of evolutionary learning rely on simple NN-like modelling strategies, employing simplifying assumptions that are common in models of artificial neural networks but not appropriate for natural gene networks [17], [21], [26].…”
mentioning
confidence: 99%